2008
DOI: 10.1038/leu.2008.353
|View full text |Cite
|
Sign up to set email alerts
|

Role of catalase in monocytic differentiation of U937 cells by TPA: hydrogen peroxide as a second messenger

Abstract: Human promonocytic cell line U937 cells can be induced to differentiate into macrophages by treatment with 12-O-tetradecanoylphorbol-13-acetate (TPA). TPA treatment induced the expression of the monocytic differentiation markers CD11b and CD36, with concomitant morphological changes. Moreover, TPA enhanced reactive oxygen species (ROS) generation in these cells, and phagocytic ability was also stimulated during differentiation. The antioxidant agent N-acetyl-L-cysteine inhibited the TPA-induced differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
64
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 57 publications
6
64
0
3
Order By: Relevance
“…14) Recent studies reported that epigenetics, such as DNA methylation and histone modifications, play pivotal roles in the progression of CKD, and some inhibitors of histone deacetylase (HDAC) exert beneficial effects against CKD. [15][16][17] Moreover, the expression of EC-SOD is known to be regulated by epigenetics in human lung cancer cells, 18,19) monocytes/macrophages, 20) and retina endothelial cells 21) ; however, limited information is currently available on EC-SOD regulation mechanisms in CKD models and the involvement of epigenetics.…”
mentioning
confidence: 99%
“…14) Recent studies reported that epigenetics, such as DNA methylation and histone modifications, play pivotal roles in the progression of CKD, and some inhibitors of histone deacetylase (HDAC) exert beneficial effects against CKD. [15][16][17] Moreover, the expression of EC-SOD is known to be regulated by epigenetics in human lung cancer cells, 18,19) monocytes/macrophages, 20) and retina endothelial cells 21) ; however, limited information is currently available on EC-SOD regulation mechanisms in CKD models and the involvement of epigenetics.…”
mentioning
confidence: 99%
“…Nevertheless, there are almost no studies addressing this issue, with just one report describing the differentiation of a promonocytic cell line into macrophages. 12 Moreover, to our knowledge, there are no reports exploring the possible role of ROS and NADPH oxidases in the differentiation of HSCs or in other haematopoietic lineages other than macrophages, including megakaryocytic differentiation, that is, the process of maturation of megakaryocytes from HSCs that releases circulating platelets. 13 K562 and HEL cells are commonly used to study different aspects related to megakaryocytopoiesis because they undergo megakaryocytic differentiation in response to phorbol esters.…”
mentioning
confidence: 99%
“…De nombreuses études ont montré l'importance du stress oxydant et sa participation à la physiopathologie de la fibrose pulmonaire [4]. On sait que les ROS sont des modulateurs de la différenciation cellulaire [2]. L'expression de la NOX4/NADPH oxydase à l'origine d'une augmentation des ROS est augmentée dans les fibroblastes pulmonaires de patients atteints de FPI [22].…”
Section: Agression Alvéolaireunclassified
“…En effet, ROS et RNS sont largement impliquées dans les réponses cellulaires physiologiques telles que les défenses anti-infectieuses, les voies de signalisation intracellulaires et la réponse mitogène. Les ROS sont des éléments modulateurs des états d'activation et de différenciation cellulaires [2,3] par l'intermédiaire des kinases/phosphatases et de leurs seconds messagers. Les ROS sont également capables de promouvoir la croissance cellulaire voire de favoriser un phénotype cancéreux, ou, à l'inverse, d'induire la sénescence et l'apoptose [4][5][6][7].…”
unclassified